Advances in computer science and ubiquitous computing : CSA & CUTE 2015 (Lecture notes in electrical engineering / editors Leopoldo Angrisani [y otros veinticuatro] ;, 2015)
This book presents the combined proceedings of the 7th International Conference on Computer Science and its Applications (CSA-15) and the International Conference on Ubiquitous Information Technologies and Applications (CUTE 2015), both held in Cebu, Philippines, December 15 - 17, 2015. The aim of these two meetings was to promote discussion and interaction among academics, researchers and professionals in the field of computer science covering topics including mobile computing, security and trust management, multimedia systems and devices, networks and communications, databases and data mining, and ubiquitous computing technologies such as ubiquitous communication and networking, ubiquitous software technology, ubiquitous systems and applications, security and privacy. These proceedings reflect the state-of-the-art in the development of computational methods, numerical simulations, error and uncertainty analysis and novel applications of new processing techniques in engineering, science, and other disciplines related to computer science.